Low aspartate aminotransferase/alanine aminotransferase (DeRitis) ratio assists in predicting diabetes in Chinese population - Xie, Wangcheng; Yu, Weidi; Chen, Shanshan; Ma, Zhilong; Yang, Tingsong; Song, Zhenshun (Frontiers in Public Health, 2022)
Background: Few studies discussed the predictive ability of aspartate aminotransferase/alanine aminotransferase (AST/ALT, DeRitis) ratio for diabetes risk. The aim of this study was to characterize the role of AST/ALT ratio in the prediction of Chinese diabetes. Methods: This retrospective cohort study analyzed a Chinese population comprising 87883 participants without diabetes at baseline between 2010 and 2016. Cox proportional hazards regression was used to identify independent risk factors. Restricted cubic spline (RCS) was performed to investigate the non-linear correlation between AST/ALT ratio and diabetes risk. Results: During a median follow-up period of 3.01 years, 1877 participants developed diabetes. Comparing the baseline characteristics, diabetes group exhibited lower AST/ALT ratio. The Kaplan-Meier curve showed that participants with low AST/ALT ratio had higher cumulative incidence, and Cox regression also demonstrated that the lower AST/ALT ratio, the higher diabetes risk (HR: 0.56, 95% CI: 0.37-0.85, P=0.006). The RCS model revealed a non-linear correlation between AST/ALT ratio and diabetes risk. In the condition of AST/ALT ratio ≤1.18, diabetes risk increased as it decreased (HR: 0.42, 95% CI: 0.19-0.91, P=0.028). In contrast, AST/ALT ratio did not independently affect diabetes when beyond 1.18. Conclusion: AST/ALT ratio is a valuable predictor of diabetes. Diabetes risk increases rapidly in the condition of AST/ALT ratio ≤1.18.